Privacy in the internet of things: A study to protect user's data in LPR systems using blockchain - Ochoa, I; Calbusch, L; Viecelli, K; de Paz, J; Valderi Leithardt; Zeferino, C. (17th International Conference on Privacy, Security and Trust, PST 2019: Proceedings, 2019)
Over the past decade, smart crime-fighting solutions have been adopted by the major cities around the world. In this context, license plate recognition (LPR) systems have been used by public safety forces to monitor vehicle movement. However, current systems store vehicle location data indistinctly, without differentiating vehicles that are under criminal investigation from those that are not. This monitoring may be used to infer personal data about the owner of the vehicle, resulting in a violation of privacy by disregarding data protection laws. This paper presents a study about the use of technologies to ensure privacy in the Internet of Things and proposes a model to protect data collected by LPR systems. Our solution uses private blockchains regulated by smart contracts to ensure that the storage of data complies with current data protection laws.